How the silent mentor program improves our surgical level and safety and nourishes our spiritual life - Mun-Kun Hong; Tang-Yuan Chu; Dah-Ching Ding (Wolters Kluwer Medknow Publications, 2017)
We briefly share our experience of using the silent mentor program in the Medical Simulation Center (MSC) of Tzu Chi University (TCU), Hualien, Taiwan, to improve our minimally invasive surgical level and patient's safety. The silent mentor program, established in 2000 by the Department of Anatomy of TCU, is a pioneering clinical skill training program based on unembalmed bodies. This program provides three valuable advantages for surgery. The first is the comprehensive understanding of the deep or rarely observed but crucial structures of the human body, which is normally difficult to achieve in living humans. The second is gaining the first experience of a novel procedure or surgery on silent mentors rather than on living humans, which is essential for young surgeons to begin their careers. The third is evaluating the safety and feasibility of a novel surgical method. In addition to surgical techniques, the most valuable point of the program is the humane ceremonies conducted for silent mentors to nourish our soul. After the workshop, all the incision wounds on every silent mentor were carefully checked and sutured in the same manner as in closing surgical wounds in a patient. Subsequently, encoffining, cremation, and thanksgiving ceremonies were solemnly held, in the hope that the medical students or trainees would imperceptibly understand their responsibility to society and the silent mentor's expectations. The Asia-Pacific Association for Gynecologic Endoscopy and Minimally Invasive Therapy, or the Taiwan Association for Minimally Gynecology Therapy, or both can consider initiating a regular silent mentor program in the MSC of TCU. It is not only intended to improve the skills of surgeons but also to allow them to participate in the interactive ceremony and thus refresh their humanitarian knowledge.